The Development and Validation of a Revised Version of the Math Anxiety Scale for Young Children - Ganley, Colleen M.; McGraw, Amanda L. (Frontiers in Psychology, 2016)
Although there is an extensive amount of research that examines the relation between math anxiety and math performance in adolescents and adults, little work has focused on this relation in young children. Recently more attention has been paid to the early development of math anxiety, and new measures have been created for use with this age group. In the present study, we report on the development and validation of a revised version of the Math Anxiety Scale for Young Children (MASYC; Harari, Vukovic, & Bailey, 2013). We conducted cognitive interviews with the 12 MASYC items with 9 children and then administered the MASYC and five newly-developed items to 296 first-, second- and third-grade children. Results from cognitive interviews show that three of the items from the original scale were being systematically misinterpreted by young children. We present a revised measure (the MASYC-R) consisting of 13 items (eight original, five newly-developed) that shows strong evidence for reliability and validity. Results also showed that a small, but meaningful, proportion of children at this age show signs of high math anxiety. Validity of the MASYC-R was supported through correlations with a number of other factors, including general anxiety, math performance, and math attitudes. In addition, results suggest that a substantial proportion of the variance in math anxiety can be explained from these other variables together. The findings suggest that the MASYC-R is appropriate for use with young children and can help researchers to answer important questions about the nature and development of math anxiety at this age.